Exploring the learning outcomes with various technologies - Proposing design principles for virtual reality learning environments - Holopainen Jani; Lähtevänoja Antti; Mattila Osmo; Södervik Ilona; Pöyry Essi; Parvinen Petri (United States, 2022)
The study compares three virtual learning environments: VR, 3D videos and 2D videos. Following Bloom’s taxonomy of learning outcomes, we measure remembering, understanding and ability to apply. We also apply the affordance theory framework to explain the differences between these virtual learning environments. Based on the results, we propose design principles for VR learning environments. The results suggest that VR has its advantages on the apply -level, or higher, as it outperforms the other two technologies at this level. In addition, several design principles are suggested, such as customized learning, challenging learning environments, multi-sensory effects, immersion, interactivity, 3D-dimensionality, engagement as well as motivation towards the content and technology. The results highlight the importance of choosing the right technology when designing virtual learning environments. This study demonstrates how virtual environment affordances and equivalent scales can be used in making those decisions.
Proceedings of the 53rd Annual Hawaii International Conference on System Sciences